Planejamento urbano e o direito à cidade : uma leitura sobre o Masterplan de Maringá/PR - Kitazawa, Hugo Minoru (2017)
In order to solve urban problems, such as lack of basic sanitation and health, mayors have used urban planning, more specifically, the preparation of strategic plans to define where to allocate the urban equipment needed to solve each of these problems. However, municipalities also lack financial resources because, even with the decentralization process, after the promulgation of the 1988 Constitution, they remain dependent on transfers of resources from the Union and the states. In this context, the Masterplan de Maringá appears as a strategic plan of economic, social and environmental development for when the city reaches one hundred years. This plan is established as a public-private partnership. The private initiative is responsible for the financial viability and the City Hall for its implementation. However, when private initiative takes the lead in this process, as in the case of the Masterplan de Maringá even though, it is represented by the Economic Development Council of Maringá, private interest prevails over the public interest, thus establishing a Process of urban entrepreneurship. In addition, although the Masterplan de Maringá is established through a council that represents the civil society of Maringa, it actually represents only a portion of the population and is denied the participation of those who do not have representation in the same council, Denying, then, the right to the city. In this context, the objective of this study is to analyze the Masterplan, as a process of constitution of agenda and formulation of public policy, in the light of the discussion about the right to the city. In order to achieve this objective, the present qualitative research used the dialogue between the adopted literature, regarding public policies, the right to the city, city marketing, growth machine theory and the process of decentralization in the scope of the federative agreement and the documents obtained, as well as the interviews with representatives of some CODEM technical chambers and a representative of the Municipal Planning and Management Council. The results show that Masterplan appears in the government agenda when CODEM places the issue of accelerated and uncontrolled growth as a public problem during a meeting between the members of the council and the head of city planning PricewaterhouseCoopers, with the participation of the municipal government. Masterplan thus emerges as an alternative to this problem. It is a plan that comprises two stages: in the first, the economic potentialities of the city are raised and, secondly, the planning of where each urban equipment will be installed. There is, therefore, a misalignment between the Masterplan and the Master Plan since, while in the first, there is the prevalence of the interests of a portion of the population and does not allow the participation of a large portion of the population, in the second, what it prevails is the public interest and not of a portion of the population and the participation of all is considered when it is time to consider what the problems are and what to do to solve them.